If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(k+5)+5=4k-10
We move all terms to the left:
3(k+5)+5-(4k-10)=0
We multiply parentheses
3k-(4k-10)+15+5=0
We get rid of parentheses
3k-4k+10+15+5=0
We add all the numbers together, and all the variables
-1k+30=0
We move all terms containing k to the left, all other terms to the right
-k=-30
k=-30/-1
k=+30
| 12(k+3)+1=9k-1 | | 5^x=16000 | | 7t=9.8 | | 5^x=1600 | | g(5)=10(5)+15 | | f(2)=25(.5)^2 | | 4(+2=3(x-2) | | f(2)=25(.5^2) | | 4(+2=3(x-2 | | 8c-42=12 | | x*0.06=10000 | | 8/9x=30 | | 7(4+q)=84 | | 4c=(2c-5)+7 | | -7x+0.5(4x-2)=-13 | | 68=91-x | | 2=x+68 | | -4*i=24 | | -4.i=24 | | s/9-99=-94 | | x^2-21x+4x=0 | | x^2-21x=-4x | | 5y+18=y+42 | | 23-8d=-1 | | 24.25=0.75x | | 5x+6+8x=39 | | 7(z-79)=77 | | Y=8-2x0 | | 11a+9=100 | | 8a+3a(5+4)=100 | | 7-4x=14+3 | | 28+y-10=10y-10-5y |